Catastrophe: a transversal mapping of colonialism and settler subjectivity. (2nd July 2016) - Kouri, Scott; Skott-Myhre, Hans
Abstract : This paper maps one mode of production within the overall machinery of genocide, appropriation, and subjugation which is colonialism: the settler subject. The settler colonial project is nothing short of a catastrophe, and the subjects who populate Indigenous territory without sanction have been produced through this catastrophe as subjects of colonial conquest, war, and settlement. While bloodshed and bigotry mark the foundational coordinates of North American nation building and settler subjectivities, we here approach catastrophe as a rupture or event that has contemporary potential to open and transforms existing sets of relations. Following Deleuze and Guattari's insistence that ruptures are opportunities to recreate ourselves in new ethical and aesthetic ways, we map the catastrophic elements of settler colonialism against catastrophe as an event that holds subversive potential. We focus on the settler because its coordinates map each of us within the political, social, and cultural cartography of twenty-first-century North America and ask: How can a transversal mapping of settlement probe aspects of settler subjectivity in order to constitute us as people accountable to colonialism? We therefore probe the affective, relational, and unconscious dimensions of the settler subject in order to develop, following Braidotti, an affirmative and active mode of engaging in the complexities of current relations within settler colonial states.